Physiological and molecular basis of gametogenesis in triploid Pacific oysters, Crassostrea gigas - Normand, Julien; Huvet, Arnaud; Fabioux, Caroline; Raguenes, Morgane; Boudry, Pierre (Actes International Conference on Shellifsh Restoration, Vlissingent, Netherlands, 12-16 Novembre 2007, 18 p., 2007)
Genetic improvement of the Pacific oyster, Crassostrea gigas, can be achieved through triploidisation, which leads to partially sterility, allowing higher growth and survival together with improved meat quality during the reproductive period. Most triploids are not fully sterile and the genetic and environmental factors involved in their partial fertility remained to be investigated. We examined gametogenesis by image analysis of histological cross sections in diploid (2n) and triploid oysters obtained either by crossing tetraploids and diploid broodstock (« natural » triploids: 3nn) or from second polar body retention (« chemical » triploids: 3nc). 5-month old triploid spat reared in a standard intensive nursery system only showed a reduction of 50% of the gonadic occupation compared with diploids. However, oysters showed retardation of gonadic maturation and 3nc exhibited higher frequency of hermaphroditism (15%) than diploids (0%). A similar analysis is currently being performed on one-year old oysters. We have also performed a comparison of reproduction between 5 to 8-month old 2n and 3nn oysters at the molecular level studying the expression of the vasa like gene (Oyvlg) by real time PCR and in situ hybridisation (ISH). Oyvlg is a specific marker of germ cell development characterized in C. gigas. Results of ISH corroborate the development of germinal stem cells and gonia in all triploid oysters as well as in diploids. As a result, the origin of the reduced fecundity of triploids is not to be searched in the first stages of gametogenesis but rather when spermatozoids and ovocytes differentiate. A significantly higher level of Oyvlg mRNA was observed in triploid compared to diploid oysters, suggesting that the transcription level of this gene is directly proportional to the structural gene dosage. However, Oyvlg mRNA level appeared much more variable between triploids than diploids. Higher sterility of triploid oysters, obtained either by selecting appropriate genotypes or adapting rearing practices would ...